Social and economic variables related with Paraquat self-poisoning: an ecological study - Jefferson Antonio Buendía; Gabriel Jaime Restrepo Chavarriaga; Andres F. Zuluaga (BMC, 2020)
Abstract Background Paraquat self-poisonings constitute a significant contributor to the global burden of suicide. Our aim was to evaluate the relationship between social and economic variables with the incidence of self-poisoning with Paraquat in the northeast of Colombia. Methods Records of 154 cases of self-poisoning with Paraquat and several socio-economic variables of six regions of northeast of Colombia were analyzed. Results Most of the cases were mestizos, farmworkers, between 20 and 29 years, with intentional exposure using the oral route. Multivariate analyses revealed significant associations among the incidence of self-poisoning with PQ with the ecological factors such as poverty greater than 30% (IRR 15.9 IC95% 5.56-44.72), land Gini index < 0.7 (IRR 7.11 IC95% 3.58-14.12), private health insurance < 40% (IRR 3.39 IC95% 1.30-8.82) and planted area > 10% (IRR 2.47 IC95% 1.60-3.80). Conclusion There is a relationship between ecological factors and, as such, this study opens the way to further developments in the field.